Life expectancy of follicular lymphoma patients in complete response at 30 months is similar to that of the Spanish general population. (22nd February 2019) - Magnano, Laura; Alonso‐Alvarez, Sara; Alcoceba, Miguel; Rivas‐Delgado, Alfredo; Muntañola, Anna; Nadeu, Ferran; Setoain, Xavier; Rodríguez, Sonia; Andrade‐Campos, Marcio; Espinosa‐Lara, Natalia; Rodríguez, Guillermo; Sancho, Juan Manuel; et al.
Summary: The use of immunochemotherapy has improved the outcome of follicular lymphoma (FL). Recently, complete response at 30 months (CR30) has been suggested as a surrogate for progression‐free survival. This study aimed to analyse the life expectancy of FL patients according to their status at 30 months from the start of treatment in comparison with the sex and age‐matched Spanish general population (relative survival; RS). The training series comprised 263 patients consecutively diagnosed with FL in a 10‐year period who needed therapy and were treated with rituximab‐containing regimens. An independent cohort of 693 FL patients from the Grupo Español de Linfomas y Trasplante Autólogo de Médula Ósea (GELTAMO) group was used for validation. In the training cohort, 188 patients were in CR30, with a 10‐year overall survival (OS) of 53% and 87% for non‐CR30 and CR30 patients, respectively. Ten‐year RS was 73% and 100%, showing no decrease in life expectancy for CR30 patients. Multivariate analysis indicated that the FL International Prognostic Index was the most important variable predicting OS in the CR30 group. The impact of CR30 status on RS was validated in the independent GELTAMO series. In conclusion, FL patients treated with immunochemotherapy who were in CR at 30 months showed similar survival to a sex‐ and age‐matched Spanish general population.